Only useful idiots would say that Cardinal Zen is calling for schism in China - TSE, Justin Kh (Institutional Knowledge at Singapore Management University, 2016)
On June 30, 2016, the Italian news outlet La Stampa put out an article written by Gianni Valente with the provocative headline, ‘Zen to Chinese Catholics: If agreement with China is signed, do not follow the Pope.’ ‘Zen,’ of course, refers not to Buddhism, but to the retired Roman Catholic bishop of Hong Kong, Joseph Cardinal Zen Ze-ken. While the article makes no mention of the word ‘schism’ in Zen’s call for Chinese Catholics to openly disagree with the Bishop of Rome, Cosmos the in Lost’s ever-energetic author Artur Rosman posted it on my Facebook timeline (as he is often wont to do) from a person who captioned it: ‘Retired Hong Kong Cardinal Calls for Schism.’ Rosman asked me if I wanted to comment, and I happily acquiesced, as this is a clear case where critical theorist Slavoj Žižek’s compliment that someone may be wrong but ‘not an idiot’ cannot be extended.